Genetic Architecture Underlying Nascent Speciation—The Evolution of Eurasian Pigs under Domestication. (21st April 2021) - Xie, Hai-Bing; Wang, Li-Gang; Fan, Chen-Yu; Zhang, Long-Chao; Adeola, Adeniyi C; Yin, Xue; Zeng, Zhao-Bang; Wang, Li-Xian; Zhang, Ya-Ping
Abstract: Speciation is a process whereby the evolution of reproductive barriers leads to isolated species. Although many studies have addressed large-effect genetic footprints in the advanced stages of speciation, the genetics of reproductive isolation in nascent stage of speciation remains unclear. Here, we show that pig domestication offers an interesting model for studying the early stages of speciation in great details. Pig breeds have not evolved the large X-effect of hybrid incompatibility commonly observed between "good species." Instead, deleterious epistatic interactions among multiple autosomal loci are common. These weak Dobzhansky–Muller incompatibilities confer partial hybrid inviability with sex biases in crosses between European and East Asian domestic pigs. The genomic incompatibility is enriched in pathways for angiogenesis, androgen receptor signaling and immunity, with an observation of many highly differentiated cis-regulatory variants. Our study suggests that partial hybrid inviability caused by pervasive but weak interactions among autosomal loci may be a hallmark of nascent speciation in mammals.